Symposium 6: Towards an ontology of networked learning - Walker, Steve; Creanor, Linda (Proceedings of the International Conference on Networked Learning, 2012)
Networked learning, conceived of as networks of people, informational resources and technologies, constitutes what has been termed a ‘highly interwined’ technology. In this paper we develop our earlier argument that sociotechnical networks can form the basis for a non-determinist theory of learning technology. Firstly, we argue that Kling et al’s sociotechnical interaction network (STIN) is compatible with a realist ontology, drawing on Fleetwood’s ‘ontology of the real’ and Lawson’s proposition of the social nature of the artefact in networks of ‘positioned practices’. This, we suggest, gives a more secure basis for the STIN concept, and provides a clear alternative to actor network theory (ANT)-based views of sociotechnical networks which do not distinguish between the influence of human and material agents. This also, we argue, provides an alternative way of anchoring concepts from the social informatics literature, often influenced by Giddens’ structuration theory, in ways that can help networked learning research. Secondly, we explore some potential implications of such an approach for theories of networked learning and learning more widely. In particular, we suggest a possible ontology of elements of learning technology. The use of the word ‘learning’ here is somewhat problematic, as it is routinely used rather loosely to describe changes at multiple levels but which are likely to have rather different underlying mechanisms. A more thorough ontology of learning technology would allow us to distinguish between these uses and identify potentially distinct mechanisms at play in different forms and levels of learning. Thirdly, we use this approach to explore how viewing learning technologies as sociotechnical networks helps to clarify our thinking about identities in social networking for personal, learning and professional purposes.